PENGARUH AUDIT TENURE, LEVERAGE, AUDIT DELAY, DAN UKURAN KAP TERHADAP AUDITOR SWITCHING - Yustita Permata Sari Syaranamual (2023)
This research aims to examine the effect of audit tenure, leverage, audit delay, and KAP size on auditor switching in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021 period. Purposive sampling is the procedure utilized to acquire samples. This research included 43 companies, with a total sample of 172 data. Techniques used in analyzing data are, the statistic descriptive test, the classical assumption test, the hypothesis test, and the logistic regression test using STATA software version 17 and Microsoft Excel. Based on the results of the analysis of the data that has been presented, it can be concluded that (1) audit tenure have a positive relationship and does not have a significant effect on auditor switching; (2) leverage has a negative relationship and does not have a significant effect on auditor switching; (3) audit delay tenure has a negative relationship and does not have a significant effect on auditor switching; (4) KAP size has a positive relationship but does not have a significant effect on auditor switching. Keywords: audit tenure, leverage, audit delay, KAP size, and auditor switching